Anatomy and histology of the mature larva of the american cotton leafworm, Alabama argillacea (Hübner, 1818) (Lepidoptera, Noctuidae) - Habib, M. E. M. (Anais da Sociedade Entomológica do Brasil, 1978)
The internal anatomy and hisiotogy of lhe different systems of the mature larva of Alabama argiliacea (Hübner, 1818) have been studied and illustrated.